IMPLEMENTATION OF CRITICAL THINKING THEORY IN LEARNING ACTIVITY AT PHILIPPINES ELEMENTARY SCHOOL - Amalia Ulfah; Hasan Mahfud; Karsono Karsono (Universitas Sebelas Maret, 2018)
Critical thinking is one of skills is needed to face the challenge in 21st century. Many countries attempted to maneuver their education system based on critical thinking indicators. One of them is Philippines. The aim of this research is to describe the implementation of critical thinking concept in elementary school was located in region Ilocos, Philippines. In this research, the descriptive qualitatif was used with the instrument is the researcher it self. The type of this research is classroom research which means that the data is natural without any action. To collect the data, researcher use observation, interview, and collect some important documentation. As a result of the study, there is implementation of critical thinking concept in learning process in elementary school, Philippines